∆E/∆E Measurements of Energetic Ions Using CVD Diamond Detectors - Ahmed Alghamdi; Lawrence Heilbronn; Luis A. Castellanos; Eric Lukosi (Journal of Spectroscopy)
Experimental and computational results of a ΔE/ΔE diamond detection system are presented. The ΔE/ΔE detection system was evaluated using energetic proton and iron beams striking thick polyethylene targets at the NASA Space Radiation Laboratory (NSRL) at Brookhaven National Laboratory (BNL). The measured data for diamond sensor A show good agreement with the Geant4 simulation. In addition, simulations have demonstrated the ability to identify hydrogen isotopes using a diamond detection system.